Protein-DNA interactions in the human beta-globin locus control region hypersensitive site-2 as revealed by four nitrogen mustards. - Temple, M D (1997)
Four nitrogen mustards have been used in this study to examine protein-DNA interactions in intact human cells, specifically at the locus control region hypersensitive site-2 (LCR HS-2) of the human beta-globin locus. Three of these nitrogen mustards are DNA-targeted by attachment of an acridine or amsacrine intercalating chromophore, while the fourth (chlorambucil) is a non-targeted mustard. The ligation-mediated PCR technique was used to determine the sites of damage at base pair resolution on DNA sequencing gels. A densitometric comparison was made between DNA damaged in intact erythroid K562 cells and in purified DNA. The intensity of DNA damage sites in the LCR HS-2 were found to differ significantly between intact K562 cells and purified DNA. At the NF-E2/AP-1 motif, pronounced damage protection was observed in DNA derived from drug treated cells. The nuclear factor- erythroid 2 (NF-E2) protein factor is thought to bind at this NF-E2/AP-1 motif in K562 cells. Other sites of protection and enhancement that corresponded to known transcription factor binding sites were also detected. These nitrogen mustards are therefore very effective compounds for detection of transcription factor binding to DNA in intact cells and are superior to other commonly used agents. The sequence selectivity of the compounds was determined using plasmid DNA and compared to that found in intact cells. The acridine-based nitrogen mustard had a preference for forming adducts at guanine bases, while the two amsacrine-based nitrogen mustards and chlorambucil formed adducts at both guanine and adenine bases.